Cognitive Semantic Properties of Titles in Foregrounding - Achilov Oybek Rustamovich (Genius Journals, 2023)
This article examines the value of titles in cross-cultural communication using the findings of cognitive-semantic features that measured value of titles as well as the expectations and evaluations they carry or the influence they have on listeners.
Keywords: expectations; evaluations; cognitive-semantic features; value of titles